Kompetensi Penyuluh Agama dalam Memberikan Bimbingan Pranikah pada Calon Pengantin di Kantor Urusan Agama Padang Barat - Lorensia, Yola Friska; Afnibar, Afnibar; Wahyuni, Yeni Fitri; Hidayat, Thaufiq; Asmawati, Asmawati (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2023)
Abstract: Religious extensions provide premarital guidance so that prospective bridal couples get a lasting marriage. But in reality, currently there are many divorces that occur at the West Padang KUA. It is suspected that religious extension have not been professional in carrying out their duties, with low competence. The objectives of this study include: first, to determine the substantive competence related to the theoretical ability of religious extension at the KUA Padang Barat. Second, to determine the methodological competence of religious extension at the KUA Padang Barat. This research uses a descriptive qualitative method. The research data sources are religious extensions, and bridal couples who have attended premarital guidance. Taking data sources using purposive sampling technique. Data collection techniques using observation and interviews. The results showed that: 1) Substantive competence related to knowledge and skills has theoretically run optimally, it's just that a small part of the extensions needs to improve his competence; and 2) Methodological competence of religious extensions, related to applicative knowledge, applicative skills and attitudes as a whole, the extension is good enough, this is indicated by the extension not only explaining the material one way, but also providing opportunities for prospective brides to ask questions and respond to the material, so that prospective brides can understand the material well.Abtsrak: Penyuluh Agama memberikan bimbingan pranikah bertujuan agar calon pasangan pengantin mendapatkan pernikahan yang langgeng. Namun kenyataannya, saat ini banyak perceraian yang terjadi di KUA Padang Barat. Hal ini diduga Penyuluh Agama belum profesional dalam menjalankan tugasnya, dengan kompetensi yang rendah. Tujuan penelitian ini untuk mengetahui kompetensi substantif dan kompentensi metodologis Penyuluh Agama di KUA Padang Barat. Penelitian ini menggunakan metode kualitatif yang bersifat deskriptif. Sumber data penelitian ialah Penyuluh Agama, dan pasangan pengantin yang sudah mengikuti bimbingan pranikah. Teknik pengumpulan data menggunakan observasi dan wawancara. Hasil penelitian menunjukkan, bahwa: kompetensi Penyuluh Agama di Kantor Urusan Agama Padang Barat mencakup pemahaman teoritis yang kuat, keterampilan komunikasi yang efektif, pemahaman terhadap nilai-nilai agama, sensitivitas terhadap masalah psikologis, dan kemampuan memberikan panduan praktis terkait pernikahan. Meskipun sebagian besar dari mereka telah berhasil mencapai tingkat kompetensi yang baik, masih ada potensi untuk peningkatan.